Efficacy of ozone against phosphine susceptible and resistant strains of four stored-product insect species - E, Xinyi; Bhadriraju, Subramanyam; Li, Beibei (My University, 2017)
The efficacy of ozone was evaluated against four economically-important stored-product insect species at 27.2 °C and 20.4% r.h. Adults of phosphine-susceptible laboratory strains and phosphine-resistant field strains of the red flour beetle, Tribolium castaneum (Herbst), saw-toothed grain beetle, Oryzaephilus surinamensis (Linnaeus), maize weevil, Sitophilus zeamais Motschulsky, and rice weevil, Sitophilus oryzae (Linnaeus), were exposed in vials to an ozone concentration of 0.42 g/m3 (200 ppm) for 1, 2, 3, 5, 6, 8, 10 and 12 h with 0 and 10 g of wheat. Initial and final mortalities were assessed 1 and 5 d after exposure to ozone, respectively. After an 8–12-h exposure to ozone, initial mortality of Sitophilus spp. and O. surinamensis was 100%, whereas the highest initial mortality of T. castaneum was 90%. A 3–4-h exposure to ozone resulted in 100% final mortality of Sitophilus spp., whereas O. surinamensis required a 6- to 10-h exposure to ozone. Adults of T. castaneum were least susceptible to ozone, and after a 10-h exposure, mortality ranged between 82 and 95%. Time for the 5 d 99% mortality (LT99) for adults of laboratory and field strains of Sitophilus spp., O. surinamensis and T. castaneum were 2.00–5.56, 4.33–11.18 and 14.35–29.89 h, respectively. The LT99 values for adults of T. castaneum and O. surinamensis were not significantly different between bioassays conducted with 0 and 10 g of wheat. The LT99 values for the laboratory strains of Sitophilus spp. in the absence of wheat were significantly lower than those obtained in the presence of wheat. Both phosphine-susceptible and -resistant strains were equally susceptible to ozone. Ozone effectively suppressed adult progeny production of all four species. Ozone is a viable alternative fumigant to control phosphine-resistant strains of these four species. © 2017 by the authors; licensee MDPI, Basel, Switzerland.
Citation: Xinyi, E., Subramanyam, B., & Li, B. (2017). Efficacy of ozone against phosphine susceptible and resistant strains of four stored-product insect species. Insects, 8(2). doi:10.3390/insects8020042
Keywords: Fumigation; Mortality; Ozone; Phosphine Resistance; Progeny Suppression; Stored-Product Insects